A rights-based analysis of the impact of public health emergencies on adolescent pregnancy in Busoga region, Uganda - Durojaye, Ebenezer (University of Pretoria, 2025)
Mini Dissertation (MPhil (Sexual and Reproductive Rights in Africa))--University of Pretoria, 2024.